2016
DOI: 10.1161/atvbaha.115.306665
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cholesterol Efflux Capacity and Atherosclerotic Cardiovascular Disease in Patients With Familial Hypercholesterolemia

Abstract: Objective-Patients with familial hypercholesterolemia (FH) are at high risk for premature atherosclerotic cardiovascular disease (ASCVD), especially because of long-term exposure to high low-density lipoprotein cholesterol levels. It has been reported that low-density lipoprotein-lowering therapy delays the onset of ASCVD. However, it still remains difficult to prevent it. Therefore, novel biomarkers and therapeutic targets are necessary to evaluate and prevent atherosclerosis in FH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 42 publications
3
66
0
3
Order By: Relevance
“…Quantitative measurement of HDL cholesterol is inadequate to assess the impact of HDL cholesterol on cardiovascular events, and improving the quality of HDL would be a better therapeutic target than simply raising HDL cholesterol level. We and others previously reported that cholesterol efflux capacity (CEC) from macrophages as an HDL function, which represents the first step of the reverse cholesterol transport pathway, is inversely associated with residual risk for atherosclerotic cardiovascular disease even after adjustment of HDL cholesterol level 710 , providing supportive evidence for the significance of HDL functionality over simple measurement of HDL cholesterol level.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Quantitative measurement of HDL cholesterol is inadequate to assess the impact of HDL cholesterol on cardiovascular events, and improving the quality of HDL would be a better therapeutic target than simply raising HDL cholesterol level. We and others previously reported that cholesterol efflux capacity (CEC) from macrophages as an HDL function, which represents the first step of the reverse cholesterol transport pathway, is inversely associated with residual risk for atherosclerotic cardiovascular disease even after adjustment of HDL cholesterol level 710 , providing supportive evidence for the significance of HDL functionality over simple measurement of HDL cholesterol level.…”
Section: Introductionmentioning
confidence: 69%
“…CEC was measured as previously reported 10 . In brief, apolipoprotein B (apoB)-depleted serum was obtained from whole serum by precipitating apoB-containing lipoproteins with a polyethylene glycol solution as described previously 53 .…”
Section: Methodsmentioning
confidence: 99%
“…26 Analysis of cholesterol efflux revealed a reduction in efflux capacity from lipid-laden macrophages when using serum from TaglnCre + vs TaglnCre - Cxcr4 fl/fl Apoe −/− mice on HFD as acceptor. Such reduced cholesterol efflux was observed without and with cAMP stimulation, which enhances cellular lipid efflux to the apolipoprotein acceptor ApoA-1 (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…First, several studies have shown an inverse association between the efficiency of patient plasma as a cholesterol acceptor in cholesterol efflux with the manifestation of various cardiovascular events. Cholesterol efflux capacity (CEC) of apoB‐depleted serum or plasma, measured in these studies, was a better predictor of CV events than HDL‐cholesterol (HDL‐C) (Bhatt and Rohatgi, ; Ogura et al, ; Rohatgi, ; Saleheen et al, ). Second, stimulation of the efflux resulted in the regression of atherosclerotic lesions (Bhatt and Rohatgi, ; Chyu and Shah, ; Fisher et al, ).…”
Section: Introductionmentioning
confidence: 99%